Landscape of research, production, and regulation in venoms and antivenoms: a bibliometric analysis - José Luis Di Fabio; María de los Ángeles Cortés Castillo; Elwyn Griffiths (Pan American Health Organization, 2021)
Objectives. To assess the productivity and visibility in research, clinical studies, treatment, use and production of antivenoms against poisonous snakes, scorpions and spiders. Methods. Bibliometric analysis of research and other activities. Articles on venoms and antivenoms published between 2000 and 2020 were retrieved from the Scopus database. The records were analyzed by bibliometric indicators including number of documents per year, journals, authors, and citation frequency. VOSviewer® v.1.6.13 was used to construct bibliometric networks for country co-authorships and co-occurrence of terms. Results. Australia, Brazil, Costa Rica and India were among the six top countries with most documents and were selected for more detailed analysis. Costa Rica was the country with the largest percentage of its publications dedicated to antivenom production and venomics. Only a few papers dealt with the issues of quality, safety, and efficacy of antivenoms or the role of the national regulatory authorities. The use of VOSviewer® allowed visualization through joint publications of networking between countries. Visualization by co-occurrence of terms showed differences in the research carried out. Conclusions. Working in a collaborative and coordinated manner these four countries could have a major impact on envenoming globally. Attention should be given not only to antivenom production but also to strengthening regulatory oversight of antivenom products.